THE LEGAL IMPLICATIONS OF BREACH OF CONTRACT IN E-COMMERCE TRANSACTIONS - Samiyono, Sugeng; Khairiyati, Fithry (JILPR Journal Indonesia Law and Policy Review, 2025)
This study, titled The Legal Consequences of Breach of Contract in E-Commerce Transactions under Law No. 19 of 2016 on Electronic Information and Transactions, addresses the legal framework governing online buying and selling activities in Indonesia, with particular focus on the consequences that arise when a seller fails to fulfil their contractual obligations. It examines how such transactions are regulated by the Electronic Information and Transactions Law and investigates the legal implications of breach of contract (wanprestasi) within that context. The research adopts a normative juridical approach, concentrating on the analysis of legal norms and principles within positive law. This doctrinal method relies primarily on written legal sources, including statutory provisions, academic literature, legal theories, and expert opinions relevant to the research topic. Data collection was conducted through library research, by reviewing and compiling both primary and secondary legal materials. These materials were then analysed using a qualitative normative method, which involves interpreting the law in a systematic and logical manner to evaluate its application to e-commerce transactions. The study ultimately aims to provide a comprehensive understanding of the legal process surrounding online commerce and to clarify the specific legal outcomes when a seller breaches their contractual duties under the prevailing legal framework.